2021
DOI: 10.54203/scil.2021.wvj52
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Profile of Escherichia coli Isolated from Bovine Subclinical Mastitis of Dairy Farms in Algeria from 2017 to 2019

Abstract: Mastitis in cows is a major problem in dairy farms leading to a decrease in the quantity and quality of milk. The aim of the present study was to examine the association between the presence of Escherichia coli (E. coli) in milk and the subclinical mastitis, and to characterize the antibiotic resistance profiles of the isolated E. coli. In the current study, a total of 360 cow raw milk samples from three dairy farms of the region of Algiers were analyzed. The analysis period lasted from Spring 2017 to Winter 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…In our study, 65.4% of dairy cows had subclinical mastitis. This number is comparable to other studies done in Algeria (Fartas et al, 2017;Meskini et al, 2021b;Ghallache et al, 2021), which showed prevalence rates of 61.6%, 62.8% and 66.4%, respectively. Nonetheless, the prevalence rate in our research was greater than that discove red by KAKI et al (2019) in Bejaia (26%) and Ferroudj et al (2021) in Algeria's Dry land area (12.9%).…”
Section: Cow Levelsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, 65.4% of dairy cows had subclinical mastitis. This number is comparable to other studies done in Algeria (Fartas et al, 2017;Meskini et al, 2021b;Ghallache et al, 2021), which showed prevalence rates of 61.6%, 62.8% and 66.4%, respectively. Nonetheless, the prevalence rate in our research was greater than that discove red by KAKI et al (2019) in Bejaia (26%) and Ferroudj et al (2021) in Algeria's Dry land area (12.9%).…”
Section: Cow Levelsupporting
confidence: 90%
“…Atypical milk production, udder oedema and systemic symptoms such as fever, lethargy and anorexia define clinical cases (Eraskine, 2001). Subclinical mastitis, on the other hand, is difficult to detect since there are no visible changes in milk or udder appearance, but it can have a substantial impact on dairy producers by lowering milk production, changing milk quality and limiting reproductive activity (Ghallache et al, 2021).…”
Section: Introductionmentioning
confidence: 99%